Analisis Faktor-faktor yang Mempengaruhi Terjadinya Fraud Pada Perbankan di Era New Normal - Ricky Ricky; Rida Ristiyana; Mahdi Mahdi; Hengky Leon; Novianty Novianty (Jurnal Akuntansi dan Pajak, 2023)
Fraud can have an impact on the destruction of the company's reputation, company losses, damage to employee morality and other negative impacts, therefore fraud is very important to pay attention to in a company. The purpose of this study is to examine and analyze the factors that influence the occurrence of fraud in banking in the new normal era. This research is a quantitative research by distributing questionnaires to respondents. The sample of this study was 100 bank employees whose samples were taken randomly. The independent variable in this study is fraud. While the dependent variable in this study is internal control, salary suitability and leadership style. The questionnaire used has been tested for validity and reliability with good categories. The data collected were analyzed using multiple linear regression analysis techniques with the help of SPSS version 23. The results of this study indicate that 1) internal control has a positive and significant effect on fraud, 2) compensation suitability has a positive and significant effect on fraud, and 3) leadership style has a significant effect on fraud. positive and significant to fraud. The results of the study can be interpreted if banks want to reduce the level of fraud, then banks must improve internal control, compensation suitability and leadership style in the banking world, especially in the new normal era.